Improvement of Anti-TNF-α Antibody-Induced Palmoplantar Pustular Psoriasis Using a 308-nm Excimer Light - Iga, Natsuko (S. Karger AG, 2012)
Anti-tumor necrosis factor (TNF)-α antibody is utilized in the treatment of a variety of chronic inflammatory conditions, including psoriasis. However, it can induce paradoxical development and/or exacerbation of psoriasis in the course of anti-TNF-α antibody treatment, which is sometimes refractory to conventional treatments. Herein, we report a case of refractory palmoplantar pustular psoriasis induced by anti-TNF-α antibody treatment, which was improved by treatment with a 308-nm excimer light. The 308-nm excimer light has less long-term risks than narrow-band UVB. The 308-nm excimer light may be a good therapeutic option for refractory psoriatic skin lesions induced by anti-TNF-α antibody therapy because of localized side effects without systemic problems, short length of treatment and low cumulative dosages of UV light.